POLICY OPTIONS IN THE MANAGEMENT OF THE RURAL FUNDS: BASED ON ISLAMIC ECONOMY - Pratiwi Kurniati (Journal of Islamic Economy and Business (JIsEB), 2020)
Introduction: This study aims to describe the management of funds related to the village by Islamic economics. Background Problems: Unemployment is a problem faced by all countries in the word, especially in developing countries, one of which is Indonesia. Unemployment is a complex problem that is influeneed by various interrelated factors, including the lack of available jobs, education and ability ini their expertise. The unemployment rate in West Kalimantan is still quite high, which is ranked nineteen out of thirty-four Provinces. Research Methods: This research is a descriptive approach literature study (library research). Results: this study concluded that management of village funds when applying the sharia system, not only emphasizes on management, but also must be based on Islamic concepts and work culture. In addition there is an additional strategy in the management of village fund with the mirror of the Islamic economy era, Umar Bin Al-Khattab that the development of human resources, property supervision, and establishment of an independent Rural Baitul Mal (BMD). BMT concept has characteristics similar to BMT, the difference in the source of the funds coming from government and user objects funds specifically targeted at local village communities. Conclusion: The concept of Baitul Mal Village itself has characteristics similar to BMT (Baitul Mal Wat Tamlik), the difference in the source of funds derived from the government and the object of the user funds specifically aimed at the local village community.